2009
DOI: 10.1590/s1517-83822009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacies of Zataria multiflora essential oil and itraconazole against disseminated Candida albicans infection in BALB/c mice

Abstract: Disseminated candidiasis is a serious problem in public health that results from the invasion of Candida species, in particular Candida albicans. The aim of this study was to compare the efficacies of Zataria multiflora essential oil and itraconazole in clearing C. albicans from the visceral organs of BALB/c mice suffered from disseminated candidiasis. Zataria multiflora essential oil was extracted using Clevenger-type apparatus and analyzed by gas chromatography mass spectrometry (GC-MS). For clearance experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In a previous study conducted by Naeini et al [25], the EOs of Z. multiflora showed a significant degree of antifungal activity (55 mm inhibition zone) against C. albicans (P < 0.05), while the oils of Z. clinopodiodes (45 mm), N. sativa (35 mm) and H. persicum (20 mm) exhibited a moderate to weak pattern of inhibition. Our results are in agreement with other studies, which showed the strong inhibitory effect of Z. multiflora on different Candida species [23,29,35] and Malassezia species [26]. In addition, the antifungal activities of the oils of Z. clinopodioides [5] and N. sativa [22] were tested against different pathogenic and saprophytic fungi.…”
Section: Resultssupporting
confidence: 93%
“…In a previous study conducted by Naeini et al [25], the EOs of Z. multiflora showed a significant degree of antifungal activity (55 mm inhibition zone) against C. albicans (P < 0.05), while the oils of Z. clinopodiodes (45 mm), N. sativa (35 mm) and H. persicum (20 mm) exhibited a moderate to weak pattern of inhibition. Our results are in agreement with other studies, which showed the strong inhibitory effect of Z. multiflora on different Candida species [23,29,35] and Malassezia species [26]. In addition, the antifungal activities of the oils of Z. clinopodioides [5] and N. sativa [22] were tested against different pathogenic and saprophytic fungi.…”
Section: Resultssupporting
confidence: 93%
“…Laboratory studies have shown that certain herbs, like ZMB and geranium, also have antimicrobial effect, similar to azole drugs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Khosravi et al . () used Z. multiflora essential oil (containing 61.29% carvacrol and 25.18% thymol) in mice infected with C. albicans . According to their results, the colony‐forming unit of Candida in the liver, spleen, lungs, brain, and kidneys reduced in the treated group compare with the control group, which likely reflects stimulation of the immune system by this plant.…”
Section: Immunological Effectsmentioning
confidence: 99%